"My Flight Arrives at 5 am, Can You Pick Me Up?": The Gatekeeping Burden of the African Academic. Issue 4 (2nd October 2021) - Tilley, Elizabeth; Kalina, Marc
ABSTRACT: Over the past decade, there has been increased awareness and discourse around the inequalities which structure North–South academic collaboration. The purpose of this discussion is to look at the other side of this dynamic: the gatekeeping burden of African scholars in facilitating Northern fieldwork within the African continent. We argue that this burden further exacerbates inherent inequalities within North–South relationships. By way of conclusion, we offer a number of practical steps that Northern researchers can take when engaging African academics which will contribute to more ethical collaboration, and a more positive and lasting impact within African institutions.